Implementation of Indonesian Traditional Games in Early Childhood Education Institutions in Sunggal District, Deli Serdang Regency - Rahimah Ulfah Harahap; Anita Yus; Ichwan Azhari (Budapest International Research and Critics University, 2022)
The purpose of this study is to describe the types of traditional Indonesian games played at the Al-Furqon Early Childhood Education Institute that can be played by children, the learning materials contained in traditional games, and the values embedded in children through the traditional game. This study uses qualitative research with a phenemenological approach, namely research by looking directly at the phenomenon, the data collection techniques used are observation, interviews, document studies and data analysis techniques using Milles and Huberman namely data reduction, data display and data verification. The results of this study found that the types of traditional Indonesian games played in Early Childhood Education institutions were free rope games, plate breaking and shell stilts. The learning materials contained in the free rope game are physical, motor, language, scientific, and social, while the values embedded in children through the free rope game are the values of hard work, agility, accuracy, and sportsmanship. The learning materials contained in the plate breaking game are physical motor, language, social, math, and science while the values embedded in children through this plate breaking game are hard work, obeying the rules, dexterity, and honesty. The learning materials contained in the shell stilt game are physical motor, language, social, science and mathematics while the values embedded in children through this shell stilt game are hard work, tenacity, independence, mutual respect and honesty.